Altered Adaptive Cellular Immune Function in a Group of Egyptian Children with Autism - Engy A. Ashaat; Khaled H. Taman; Naglaa Kholoussi; Mona O. El Ruby; Moushira Erfan Zaki; Maged A. El Wakeel; Neveen A. Ashaat; Samira Ismail Ibrahim (Journal of Clinical and Diagnostic Research, 2017)
Introduction: There is a growing evidence of immune system alteration in children with Autism Spectrum Disorder (ASD). These changes may include higher levels of pro-inflammatory cytokines in plasma, Cerebrospinal Fluid (CSF) and brain cells. Aim: To evaluate the imbalance of the immune system in autism through correlating some immunological markers (C3, C4, CD4, IL12 and IL17) with severity of ASD. Materials and Methods: The current case-control study included 120 subjects, 60 autistic children and 60 healthy control obtained from the Clinical Genetics Clinic, National Research Centre, Egypt from the period between December 2014 to December 2016. All candidates were subjected to full clinical evaluation in addition to ElectroEncephaloGraphy (EEG), hearing test and estimation of interleukins (IL12- IL17), C3-C4, CD4 levels in blood samples. Independent t-test, Chi-square test or McNemar test were used to analyse the data. Results: The levels of IL12 (27.47 ±7.15) and IL17 (1630.46±310.42) were significantly higher, (p= 0.026, 0.005) respectively, while levels of CD4 were significantly lower (37.93±3.25), (p<0.001) in autistic children compared to controls; however, there was no significant difference in C3 and C4 between the two groups. High statistically significant difference between autistic children with moderate and severe ASD in CD4 levels were seen, (p=0.018). Conclusion: Autistic children may suffer from immunological dysfunction. Further efforts should be exerted to find out the relation between immune imbalance and the progression of ASD.